(untitled) (Journal of Engineering, 2018)
To damp the low-frequency oscillations which occurred due to the disturbances in the electrical power system, the generators are equipped with Power System Stabilizer (PSS) that provide supplementary feedback stabilizing signals. The low-frequency oscillations in power system are classified as local mode oscillations, intra-area mode oscillation, and interarea mode oscillations. Double input multiband Power system stabilizers (PSSs) were used to damp out low-frequency oscillations in power system. Among dual-input PSSs, PSS4B offers superior transient performance. Power system simulator for engineering (PSS/E) software was adopted to test and evaluate the dynamic performance of PSS4B model on Iraqi national grid. The results showed that after installing the PSS in a specific plant the oscillation of rotor angle, bus frequency, speed, power flow is better than without PSS during the disturbances that occurred during the simulations. All the PSS/E simulation and tests were done in the National dispatch center (NDC) laboratory, Ministry of Electricity.